Evaluation of the Implementation of the Exclusive Breast Milk (ASI) Program Policy in the City of Semarang - Kusuma, Aurima Hanun; Raharjo, Bambang Budi; Farida, Eko (Universitas Negeri Semarang, 2024)
Exclusive breastfeeding is an important policy to ensure the health of infants and mothers. Semarang, as one of Indonesia's metropolitan cities, faces challenges in implementing this policy. Evaluation of the exclusive breastfeeding program is necessary to understand its implementation success and influencing factors. This study aims to evaluate the implementation of the exclusive breastfeeding policy in Semarang. The method used is qualitative research with a case study approach. Data were collected through in-depth interviews with health officials, lactating mothers, and relevant stakeholders in Semarang's exclusive breastfeeding policy implementation. The research findings indicate several challenges in the implementation, such as low public awareness of the importance of exclusive breastfeeding and inadequate government supervision. Based on the research results, evaluation of input from various research informants indicates that the planned breastfeeding program has been well communicated despite some obstacles. Program evaluation is conducted monthly by health centers through recording and reporting. Evaluation of the implementation of the exclusive breastfeeding policy in Semarang is carried out using an output evaluation model, assessing the coverage rate of exclusive breastfeeding in Semarang, which shows an increase in the coverage rate of exclusive breastfeeding.